Protection Between Islamic Law and Law No. 13 of 2003 concerning Manpower (Case Study of PT Gunbaster Nickel Industry) - Intan Delima; Nurenzy Turahmi; Ray Habib Bayhaqqi; Zeinadib; Bela Amelia (ISNU Sumatera Utara, 2024)
Labor protection is an important aspect in creating fair industrial relations, both from the perspective of Islamic law and positive Indonesian law. The employment case of PT Gunbuster Nickel Industry (PT GNI) shows that there are problems regarding the fulfillment of workers' rights, ranging from work accidents, occupational safety and health protection, fulfillment of wage rights, to freedom of association. This study aims to analyze the legal protection of labor in the perspective of Islamic law and Law Number 13 of 2003 concerning Manpower and examine its implementation in the case of PT Gunbuster Nickel Industry. The research methods used are normative juridical research with a statutory approach, a conceptual approach, and a case approach. Research data was obtained through literature studies on laws and regulations, legal literature, and sources related to PT GNI's case. The results of the study show that Islamic law through the concept of maqashid al-syariah provides protection for workers through the principles of justice, protection of the soul (hifz al-nafs), and protection of property (hifz al-mal). Indonesia's positive law provides protection through labor regulations, occupational safety, social security, and protection of freedom of association. The case of PT GNI shows that there is a gap between normative provisions and the practice of implementing industrial relations because problems related to work safety, wage rights, and worker protection are still found. The conclusion of this study shows that labor protection already has a strong legal basis, but its effectiveness requires more optimal supervision and law enforcement.